Interactions of Foundation Pit on the Underlying Adjacent Existing Underground Structures - Wanzhong Xu; Baohua Liu; Jingshuo Liu; Chun Guo (Geofluids)
The influence of foundation pit excavation on deformation and stability of the supporting structure of underlying adjacent existing tunnel is a comprehensive geotechnical engineering problem, including unloading effect of foundation pit excavation and the coupling effect of deformation of the tunnel surrounding rock and supporting structure. Using numerical calculation methods, this paper changes the different excavation depths and widths of foundation pit and discusses the evolution law about force and deformation of tunnel supporting structure, and the changing relationship of the axial force of tunnel anchor with the distance between foundation pit and tunnel is obtained and compares the influence of different excavation way of foundation pit on the axial force of anchor rod near the existing tunnel. It is found that with the increase of distance between foundation pit and tunnel, the axial force of anchor rod at the top of tunnel under the foundation pit entirely symbolizes a trend of increases first and then decreases, the axial force of the leftmost anchor rod changes from pressure to tension, then decreases gradually. When the foundation pit depth increases, the axial force of the anchor rod at the top of the tunnel increases, the axial force of the leftmost anchor rod decreases, and the width of foundation pit absolutely has little effect on the axial force of the leftmost and the top tunnel.